1962
DOI: 10.1111/j.1365-2494.1962.tb00290.x
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Winter Grass From a Row Crop of Cocksfoot and Lucerne

Abstract: A crop of cocksfoot and lucerne in alternate rows was subjected to various autumn treatments for winter pasture. The yield of grass in winter, and the effect of autumn and winter treatments upon yield and composition in the following spring, are reported and discussed. Maximum yield of winter grass was achieved by resting from an early date and applying nitrogenous fertilizer. The response to fertilizer applied in August and mid‐September for winter grass production was as good as that obtained on ordinary swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1964
1964
1979
1979

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…6 indicate that growth during the cold winter months is appreciable, although much of the herbage produced remains unharvested and is lost. There is no evidence to support the view that this growth is made at the expense of the stubble (Cowling, 1962), so that it is evident that winter growth can proceed on the basis of current photosynthesis. When temperature and radiation increase in spring, crop growth rates increase very markedly.…”
Section: Sum Of Harvestable Cut Herbage From the Different Cutting Rementioning
confidence: 93%
“…6 indicate that growth during the cold winter months is appreciable, although much of the herbage produced remains unharvested and is lost. There is no evidence to support the view that this growth is made at the expense of the stubble (Cowling, 1962), so that it is evident that winter growth can proceed on the basis of current photosynthesis. When temperature and radiation increase in spring, crop growth rates increase very markedly.…”
Section: Sum Of Harvestable Cut Herbage From the Different Cutting Rementioning
confidence: 93%
“…Rayburn and coworkers (1980) concluded that the best time to begin accumulating tall fescue depends on a variety of management considerations, such as the area of tall fescue, the amount of other available forages, and the nutritional needs of the livestock. Cowling (1962) noted that if the accumulation period of alfalfa and orchardgrass is too long, alfalfa will drop its leaves and rapidly decrease in quality. Collins and Taylor (1980) in Kentucky demonstrated that DM losses of alfalfa-orchardgrass began earlier for forage accumulated in August than forage stockpiled in September.…”
Section: Length Of Accumulation Periodmentioning
confidence: 99%